Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Short‐term homeostatic regulation of blood/interstitial fluid Ca 2+ concentration by the scales of anadromous sea trout Salmo trutta L. during smoltification and migration - Leanna Jamieson; Angel Waters; Kaitlyn E. Ho; Harvey Y. S. Chan; Jacky T. Hung; Sarah E. Webb; Ching Man Chan; Alan M. Shipley; John G. Williamson; Jon Beer; Chevonne Angus; Andrew L. Miller (Journal of Fish Biology, 2021)
The elasmoid scales of anadromous sea trout Salmo trutta L. represent a significant internal reservoir of Ca 2+ . Although more is known about long‐term remodelling of scales in response to calciotropic challenges encountered during smoltification and migration, very little is known about the contribution made by scales to the short‐term, minute‐to‐minute regulation of Ca 2+ homeostasis in the extracellular fluid (ECF) during these phases of the life cycle. This gap in the knowledge is partly due to the technical challenges involved in measuring small Ca 2+ fluxes around the scales of live fish in real time. Here, this study describes exfoliating, mounting and culturing scales and their resident cells from parr, smolt and adult sea trout from a freshwater environment, as well as from adult sea trout caught in sea or brackish water. All the scales were then examined using an extracellular, non‐invasive, surface‐scanning Ca 2+ ‐sensitive microelectrode. The authors quantified the Ca 2+ fluxes, in the absence of any systemic or local regulators, into and out of scales on both the episquamal and hyposquamal sides under different extracellular calcemic challenges set to mimic a variety of ECF‐Ca 2+ concentrations. Scales from the life‐cycle stages as well as from adult fish taken from sea, brackish or fresh water all showed a consistent efflux or influx of Ca 2+ under hypo‐ or hypercalcemic conditions, respectively. What were considered to be isocalcemic conditions resulted in minimal flux of Ca 2+ in either direction, or in the case of adult scales, a consistent but small influx. Indeed, adult scales appeared to display the largest flux densities in either direction. These new data extend the current understanding of the role played by fish scales in the short‐term, minute‐to‐minute homeostatic regulation of ECF‐Ca 2+ concentration, and are similar to those recently reported from zebrafish Danio rerio scales. This suggests that this short‐term regulatory response might be a common feature of teleost scales.

Identification of Ca2+ signaling components in neural stem/progenitor cells during differentiation into neurons and glia in intact and dissociated zebrafish neurospheres - Man Kit Tse; Ting Shing Hung; Ching Man Chan; Tiffany Wong; Mike Dorothea; Catherine Leclerc; Marc Moreau; Andrew L. Miller; Sarah E. Webb (Science China Life Sciences, 2018)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)